English around the world : an introduction - Schneider, Edgar W. (Edgar Werner), 1954- (Cambridge introductions to the English language, 2020)
"The global spread of English has had widespread linguistic, social, and cultural implications, affecting the lives of millions of people around the world. This textbook provides a lively and accessible introduction to world Englishes, describing varieties used in countries as broad-ranging as America, Jamaica, Australia, Africa, and Asia, and setting them within their historical and social contexts. Students are guided through the material with chapter previews and summaries, maps, timelines, lists of key terms, discussion questions and exercises, and a comprehensive glossary, helping them to understand, analyze, and compare different varieties of English, and apply descriptive terminology. The book is accompanied by a useful website, containing textual and audio examples of the varieties introduced in the text, and links to related sources of interest. Providing essential knowledge and skills for those embarking on the study of world Englishes, this book has become the leading introduction to the subject"--